Contract Management System among Selected Construction Companies in Qatar - Polinar, Mark Anthony N.; Dela Cruz, Gerelyn S. (Future Science / FSH-PH Publications, 2023)
The State of Qatar's construction industry proliferates, attracting international investors and contractors to large-scale projects. This growth, however, is accompanied by an inevitable increase in claims and disputes, causing significant delays and additional costs to the project. The study’s focus is to understand better the practical problems affecting the contract management system’s efficiencies in selected construction companies in Qatar. A descriptive correlational research design method was carried out using a survey questionnaire to determine the degree of importance and awareness of the contract management system in terms of risk, change, and claim management. Also, the results revealed that employees perceived risk, change, and claim management as integral parts of the contract management system. A Pearson correlation coefficient was used to test the correlation between the variables covered in the study, and the statistical evidence concluded that there is a significant strong linear relationship between the degree of importance and awareness in the contract management system. Therefore, based on the literature presented in this study and the data gathered from fifty-two respondents who voluntarily participated in the survey, the authors recommended that the organizations must embrace these contract management methods to cut costs, shorten lead times, and boost profitability: clear dispute resolution procedures, precise change control procedures, proper record keeping, effective risk mitigation plan, competent team members, and the organization's capability and readiness to resort to arbitration when other dispute resolution procedures are exhausted.